(untitled) (ARQUISUR Revista, 2023)
This article explores and analyzes a segment of the journal Arquitectura, published by the Uruguayan Architects Association (SAU, for its Spanish initials), focusing on the discipline challenges that arose between 1914 and 1940. While 1914 marks the founding year of the SAU and the onset of World War I, 1940 does not represent a definitive milestone but it roughly coincides with the construction of the new building for the Faculty of Architecture and the intensification of World War II, which began in 1939. During this period, Uruguayan architecture displayed a significant inclination towards the modern movement. Among the various topics addressed in the journal, five were chosen for their publication frequency, clarity, and relevance. These topics are education, the consolidation of a professional corporation, the transition from "Fine Arts" to "Modernity," housing challenges, and the debate on urbanism as a discipline, with particular emphasis on international visits. Although the analysis of these topics is brief, the aim is to identify the main currents of debate from a critical perspective, leading to a set of preliminary conclusions that encourage contemporary reflection.